Unveiling the digital gym: A phenomenological dive into online physical education pedagogy - Peralta, Princes Lloyda (Physical Education and Sports: Studies and Research, 2025)
Background: The COVID-19 pandemic necessitated a rapid shift to online learning, posing significant challenges for traditionally hands-on subjects like Physical Education (PE). Limited student engagement, digital accessibility issues, and the need for pedagogical adaptation became major concerns for PE instructors. Objectives: This study aims to explore the lived experiences of PE instructors in adapting to online instruction, identifying the strategies, challenges, and innovations they employed to maintain instructional effectiveness. Methods: A qualitative research design utilizing Interpretative Phenomenological Analysis (IPA) was adopted to gain deep insights into instructors’ experiences. Purposive sampling was used to select seven PE instructors from urban and rural institutions, ensuring diverse teaching contexts. Data were collected through semi-structured interviews, and thematic analysis was conducted to identify key adaptation strategies. Results: Five major themes emerged from the findings: (1) Adaptation to Online Instruction, where instructors restructured their teaching approaches to accommodate digital platforms; (2) Effective Use of Digital Tools, emphasizing the role of online resources in enhancing instructional delivery; (3) Innovative Approaches to Engagement, detailing gamification techniques and interactive pedagogies; (4) Equitable Access Strategies, addressing disparities in internet connectivity and learning resources; and (5) Assessment of Success and Progress, highlighting novel evaluation methods tailored for online PE instruction. These themes collectively form the "Navigating Instructional Delivery Through Innovation, Technology, Engagement, and Equity" framework. Conclusions: The study provides valuable insights into how PE instructors have innovatively adapted to online learning, ensuring student engagement and equitable access to education. The findings offer implications for policy-making, teacher training programs, and the future integration of technology in PE instruction. Future research should explore student perspectives and the long-term impact of digital PE on learning outcomes.